THE ROLE OF THE DIRECTION AND PEDAGOGICAL COORDINATION AT THE MUNICIPAL PUBLIC SCHOOL, IN VIEW OF DEMOCRATIC-PARTICIPATORY MANAGEMENT IN THE IMPROVEMENT OF TEACHING - Teixeira Lima, Larissa; Rocha Lopes, Juliana; Paula Bochi, Ana; Maria Bochi Silva, Élida; Pereira Gusmão, Jacqueline; da Silva Dias, Edcler; Cristina de Oliveira Amorim Pedro, Viviane; de Souza Oliveira, Renata; Soprani Santos, Leni; Manuela Bárbara Belizário, Carla (Revista Gênero e Interdisciplinaridade, 2024)
The present article is part of the work of completion of a distance learning course in School Management from the Campos Elíseos College, and aims to present the role of members of the public school management team, as a basis in democratic-participatory management . In addition, it was sought to present the importance of adopting as a conception of democratic-participatory school management in the search for quality public education. The article is based on the bibliographic research obtained in the classes developed during the course. It was found that the functions attributed to the management team as a whole are numerous and of great responsibility. Thus, these professionals need to work their best to guarantee their students a significant and quality teaching. It is concluded that being a professional of education means being always built, in a process that starts, but has no end.